Prevalence of cardiac pathology and relation to mortality in a multiethnic population hospitalised with COVID-19 - Roxy Senior; Ashish Patel; Emma Howard; Reinette Hampson; Gabriel Bioh; Christina Botrous (Open Heart)
Objective To determine the prevalence of cardiac abnormalities and their relationship to markers of myocardial injury and mortality in patients admitted to hospital with COVID-19.Methods A retrospective and prospective observational study of inpatients referred for transthoracic echocardiography for suspected cardiac pathology due to COVID-19 within a London NHS Trust. Echocardiograms were performed to assess left ventricular (LV), right ventricular (RV) and pulmonary variables along with collection of patient demographics, comorbid conditions, blood biomarkers and outcomes.Result In the predominant non-white (72%) population, RV dysfunction was the primary cardiac abnormality noted in 50% of patients, with RV fractional area change <35% being the most common marker of this RV dysfunction. By comparison, LV systolic dysfunction occurred in 18% of patients. RV dysfunction was associated with LV systolic dysfunction and the presence of a D-shaped LV throughout the cardiac cycle (marker of significant pulmonary artery hypertension). LV systolic dysfunction (p=0.002, HR 3.82, 95% CI 1.624 to 8.982), pulmonary valve acceleration time (p=0.024, HR 0.98, 95% CI 0.964 to 0.997)—marker of increased pulmonary vascular resistance, age (p=0.047, HR 1.027, 95% CI 1.000 to 1.055) and an episode of tachycardia measured from admission to time of echo (p=0.004, HR 6.183, 95% CI 1.772 to 21.575) were independently associated with mortality.Conclusions In this predominantly non-white population hospitalised with COVID-19, the most common cardiac pathology was RV dysfunction which is associated with both LV systolic dysfunction and elevated pulmonary artery pressure. The latter two, not RV dysfunction, were associated with mortality.